2000
DOI: 10.1177/03635465000280041701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tibial Tunnel Enlargement after Anterior Cruciate Ligament Reconstruction Using Patellar Tendon Autograft or Allograft

Abstract: This retrospective study was designed to compare tibial tunnel enlargement in patients with autograft or allograft anterior cruciate ligament reconstructions. The changes were related to position of the tibial tunnel and clinical outcome. Twenty-six patients with autograft reconstructions and 41 with allograft reconstructions were studied at a mean follow-up of 59 months (range, 41 to 84) after surgery. The average tunnel enlargement on the anteroposterior view was 2.2 mm (SD, 2.5) for autografts and 2.8 mm (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 12 publications
0
52
1
Order By: Relevance
“…Webster et al found significant correlation between tibial tunnel enlargement and anterior knee laxity [8] . Bone tunnel widening is more associated with many factors like type of graft, graft fixation systems elastic or rigid, single or double bundle fixation, and aggressive rehabilitation [18] . The biological theory states that release of TNF, interleukins, and nitric oxide present in the synovial fluid can cause osteolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Webster et al found significant correlation between tibial tunnel enlargement and anterior knee laxity [8] . Bone tunnel widening is more associated with many factors like type of graft, graft fixation systems elastic or rigid, single or double bundle fixation, and aggressive rehabilitation [18] . The biological theory states that release of TNF, interleukins, and nitric oxide present in the synovial fluid can cause osteolysis.…”
Section: Resultsmentioning
confidence: 99%
“…The biological theory states that release of TNF, interleukins, and nitric oxide present in the synovial fluid can cause osteolysis. The mechanical reasons for tunnel widening are graft tunnel micro motion in suspensory fixation, stress shielding proximal to the interference screw and nonantomical graft fixation [18,19,20] . As menisci along with cruciate ligaments also has important role in biomechanical stability, we have tried to evaluate incidence of tunnel widening and knee instability after ACL reconstruction and compare them in two groups: those with meniscal repair and those with without repair.…”
Section: Resultsmentioning
confidence: 99%
“…In our cases, we had maintained standard protocol of rehabilitation of 2 weeks immobilization in extension followed by gradual knee bending up to 90 degree and full weight bearing at the end of one month. We had used transportal technique to drill the femoral tunnels to place the footprint as anatomical as possible as it was found that non anatomical or anterior tibial tunnel placement was found to have higher tunnel enlargement due to mechanical stress on the graft [20] . The etiology of tunnel enlargement is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Possible factors responsible for bone resorption include mechanical theory which states that there is a micromotion of the graft relative to the tunnel wall which causes synovial fluid bathing of the graft, leading to an inflammatory response in the tunnel. Also stress shielding of the tunnel wall proximal to the interference screw can cause weakening of the bone [6,20,21] Biological factors include nonspecific inflammatory response cells, heat necrosis due to drilling, cytokine response like TNF, interleukin-6, nitric oxide from the synovial fluid and foreign body response to allograft [22,23] There are different patterns of osteolysis at tibial tunnel described by Peyrache where patellar tendon bone graft was fixed with screw. These are cone type, cavity type and line type [7] We evaluated similar changes in our patients and tried to evaluate its clinical and functional correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into consideration the distance from the fixation to the joint surface, the rates range from 0% to 23% for grafts subjected to anatomical fixation (4) and from 47% to 73.9% for those fixed at a distance from the joint surface (3) . Although many studies have reported occurrences of enlargement, none have proven that it is clinically significant or that it is related to surgical failure rates (1,4,5,6) . Its mechanism is also not fully understood.…”
Section: Introductionmentioning
confidence: 99%